Kinetics and Thermodynamics Equilibrium of Nickel Metal Ions Sorption onto Carbon Nanofibers Irradiated by Ultrasonic Energy - Alimin Alimin; La Ode Ahmad Nur Ramadhan; La Ode Ahmad; Fahmiati Fahmiati; Darwin Ismail; Ahmad Zaeni; Muhammad Zakir Muzakkar; Intan Intan; La Agusu; Indriana Kartini; Sri Juari Santosa (UNIVERSITAS SEBELAS MARET (UNS), 2024)
In this work, we investigated the effects of the heavy metal initial concentration and the pH on the sorption of heavy metal ions onto carbon nanofibers using the liquid phase adsorption technique under ultrasonic energy irradiation. These data were then used to study thermodynamic aspects such as sorption capacity and energy and kinetic parameters such as kinetic model, reaction order, and rate constant of heavy metal sorption on carbon nanofibers. We found that the increase of the heavy metal (nickel) initial concentration was proportional to the amount of heavy metal adsorbed onto carbon nanofibers. The highest uptake of the heavy metal ions' amount onto carbon nanofibers in equilibrium (qe) was 244.00 mg.g-1, achieved at the pH of 8. Langmuir and Freundlich's isotherms were used to find the best-fitted isotherms model. The Langmuir isotherm best fits the sorption equilibrium of the heavy metal ions on Carbon nanofibers. Bothipseudo-first and pseudo-second orders studied the sorption and kinetic parameters of heavy metals on carbon nanofibers. The sorption kinetics model was fitted to the pseudo second-order. Based on the value of Gibbs free energy, the metal ions' sorption onto carbon nanofibers occurs spontaneously.